Upregulation of Tumor Necrosis Factor-α-Induced Protein 8-Like 2 mRNA Is Negatively Correlated with Serum Concentrations of Tumor Necrosis Factor-α and Interleukin 6 in Type 2 Diabetes Mellitus. (24th May 2017) - Liu, Yongliang; Wang, Xinmei; Zhao, Yan; Zhao, Peiqing; Wang, Lianqing; Zhai, Qiaoli; Zhang, Xiaowei; Tian, Wenxiu; Xiang, Xinxin; Li, Tao
Abstract : Background . Tumor necrosis factor- α -induced protein 8-like 2 (TIPE2 or TNFAIP8L2) is a negative regulator of natural and adaptive immunity. The role of TIPE2 in type 2 diabetes mellitus (T2DM) remains unknown, although TIPE2 plays key roles in preserving inflammatory homeostasis. Methods . TIPE2 expression was measured by Western blotting and real-time polymerase chain reaction (RT-PCR) in peripheral blood mononuclear cells (PBMCs) isolated from T2DM patients and healthy controls, and tumor necrosis factor- α (TNF- α ), high-sensitivity C-reactive protein (hsCRP), interleukin 6 (IL-6), and other related biometabolic parameters were detected using a nephelometer or by ELISA. Differentiated THP-1 cells were exposed to siTIPE2 and TIPE2 adenovirus. Results . TIPE2 was significantly increased in PBMCs from T2DM patients compared with those from healthy controls and was negatively correlated with serum TNF- α, IL-6, and hsCRP concentrations but positively correlated with HbA1c and LDL-C in T2DM patients. High glucose treatment (50 mmol/L) can upregulate the expression of TIPE2 and cytokine secretion in differentiated THP-1 cells. siTIPE2 infection exacerbated the increased TNF- α and IL-6 concentrations in differentiated THP-1 cells under high glucose conditions (50 mmol/L), while infection with TIPE2 adenovirus reversed the increased TNF- α concentration. Conclusions . The present study indicates that TIPE2 may participate in T2DM by regulating TNF- α production.